Clifford's puppy days - Bridwell, Norman (New York : Scholastic, 1989)
Recounts the antics of big, lovable Clifford when he was a very small puppy.
1.8
K-3
Keywords: Dogs -- Juvenile fiction; Dogs -- Fiction; Size -- Fiction; Dogs -- Fiction; Size and shape -- Fiction